Editorial: ulcer‐related vs non‐ulcer‐nonvariceal upper gastrointestinal bleeding—which has worse outcomes?. Issue 6 (27th February 2019) - Yuan, Yuhong; Leontiadis, Grigorios I.
Abstract : Linked Content This article is linked to Sey et al paper. To view this article, visit https://doi.org/10.1111/apt.15092 .